2016
DOI: 10.1161/circulationaha.116.023116
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA Methylation of Long Noncoding RNA H19 in Calcific Aortic Valve Disease Promotes Mineralization by Silencing NOTCH1

Abstract: These findings indicate that a dysregulation of DNA methylation in the promoter of H19 during calcific aortic valve disease is associated with a higher expression of this lncRNA, which promotes an osteogenic program by interfering with the expression of NOTCH1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
144
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 40 publications
8
144
0
Order By: Relevance
“…Silencing H19 inhibits RUNX2 and BMP2, classic markers of osteogenic calcification, and reduced mineralization, while overexpression had the opposite effects. Furthermore, it was found that H19 overexpression reduced activity on the NOTCH1 promoter, identifying H19 as a novel suppressor of NOTCH1 and therapeutic target in CAVD [42]. …”
Section: Molecular Pathways For Aortic Valve Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing H19 inhibits RUNX2 and BMP2, classic markers of osteogenic calcification, and reduced mineralization, while overexpression had the opposite effects. Furthermore, it was found that H19 overexpression reduced activity on the NOTCH1 promoter, identifying H19 as a novel suppressor of NOTCH1 and therapeutic target in CAVD [42]. …”
Section: Molecular Pathways For Aortic Valve Calcificationmentioning
confidence: 99%
“…Hemodynamic shear stress caused an increase in anti-osteogenic and anti-inflammatory networks in wildtype, but not NOTCH1 +/− endothelial cells, indicating that endothelial NOTCH1 mediates the protective effects of shear stress [43]. The authors also found a discrepancy in H3K27ac at NOTCH1-bound enhancers, which correlated with an alteration in the downstream transcriptome, suggesting that this mutation alters the epigenetic profile in endothelial cells [42]. In another related study, the same group discovered that Matrix Gla Protein (MGP) is a direct target of NOTCH1 in human aortic VECs and responds to shear stress in a NOTCH1-dependent manner.…”
Section: Molecular Pathways For Aortic Valve Calcificationmentioning
confidence: 99%
“…Understanding the molecular mechanism of warfarin-induced aortic valve calcification is important to develop preventives or therapeutics. It has recently been shown that the long noncoding RNA (lncRNA) H19 in aortic valve interstitial cells (AVICs) 4 regulates Notch1 by preventing recruitment of p53 to the Notch1 promoter and thereby promotes calcification (10) indicating that p53 functions a transcription factor during AVIC calcification. Calcification of vascular smooth muscle cells can be induced with a 10 μ M therapeutic level of warfarin (11,12).…”
mentioning
confidence: 99%
“…That causal link has been elusive until the recent and impressive work by Hadjj et al, in this issue of Circulation , demonstrated that the promoter region of the long non-coding (lnc) RNA H19 is hypomethylated in patients with CAVD. 3 This hypomethylation, in turn, increases H19 expression in the valve interstitial cells (VICs) where it prevents NOTCH1 transcription by seemingly blocking or outcompeting p53’s recruitment to the NOTCH1 promoter. Thus, H19 appears to be the missing link (or lncRNA, if you will) connecting NOTCH1 to idiopathic CAVD.…”
mentioning
confidence: 99%
“…13 CDH11 overexpression causes CAVD in mice 14 and has been found to be upregulated in cases of human idiopathic CAVD (Figure). 15 Additionally, Hadjj et al showed that knockdown of H19 decreased CDH11 by ~30% in human VICs cultured in osteogenic medium (Supplemental Figure 1 in 3 ). Interestingly, CDH11 transcription was not increased by osteogenic medium, suggesting that H19 expression may directly affect CDH11 through repression of NOTCH1 .…”
mentioning
confidence: 99%